(untitled) (Universal International Scientific Journal, 2026)
This article discusses the impact of social networks on the psyche and behavior of adolescents. It is no exaggeration to say that the social network that attracts adolescents has become a pressing problem of today. The human psyche and behavior are a delicate matter. This is known to everyone. The period of adolescence brings about significant physiological and neurohumoral changes in our human body. These changes, in turn, cause a number of negative consequences.